Nationalism in Islamic Education: KH. Hasyim Asy'ari's Perspective - Astuti, Nita Yuli (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2024)
This study aims to analyze the concept of Islamic education in strengthening the nationalism character of students from the perspective of KH. Hasyim Asy'ari. Using a literature study, this research found that the concept of nationalism education according to KH. Hasyim Asy'ari is reflected in his teachings which explain that love for the country is part of faith, while strengthening faith is the main goal in the concept of tawhid taught in Islamic education. This connection is strengthened by Hasyim Asy'ari's opinion that integrates religious teachings with love for the nation and state, including the understanding that maintaining the integrity of the state and contributing to the welfare of society is a form of practicing Islamic values. This study also found that in Hasyim Asy'ari's perspective, the concept of Islamic education that supports the values of nationalism is learning that actualizes moral and ethical values such as honesty, justice and social responsibility as the foundation for strengthening the spirit of nationalism. According to him, this is an important foundation in maintaining unity in diversity. With these findings, this study contributes to providing new insights into the relevance of Hasyim Asy'ari's teachings in the context of Islamic education and the character of nationalism, showing how the integration of religious values and nationalism can form individuals who are religiously devout and love the country, and are ready to contribute to the progress of the nation